Cross-cultural awareness in game-based learning using a TPACK approach - Amelia Jati, Robert Jupit; Jacey Lynn, Minoi; Arnab, Sylvester; Yeo, Alvin Wee (2011)
Our paper focuses on promoting cultural awareness through game-based learning using the Technological Pedagogical Content Knowledge (TPACK) framework. The TPACK framework,proposed by Mishra and Koehler(2008), is widely used as an organising frame for the development of education technology. This framework takes into consideration the use of effective pedagogical practice to enhance teaching and learning environment. Hence, we are looking at using the framework to promote the development of cultural awareness technology and content,by introducing the extended TPACK. We draw a need to expand the TPACK by incorporating another dimension that is the key cultural elements, within the Pedagogy, Content, and Technology components, to mutually interact, in order to promote cross-cultural awareness on agame-based learning (GBL)platform. Specifically, the content-knowledge for promoting cultural awareness would include key elements of cultures. The pedagogical-knowledge includes methods and strategies to promote and encourage understanding and respect of a culture. The advancement of game technology can be capitalised to encourage and sustain engagement in a learning platform. Presently, the work on cross-culture awareness in games is still very limited. As such, the aim of the development of a GBL platform using the extended cultural TPACK framework would be to expose learners to culturally diverse scenarios and engage as well as expose learners to knowledge of the different cultures in myriad ways.